Pengaruh Kemandirian Belajar dan Kuriositas terhadap Prestasi Belajar Ilmu Pengetahuan Alam - Erwinsyah, Erwinsyah; Wildan, Ahmad Chairun (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
Based on preliminary observations of teachers in several Junior High Schools in the Bekasi Regency, students' achievement in science subjects was still low. The purpose of this study was to determine the effect of learning independence and curiosity both together and partially on the science learning achievement of SMPN's students in the Bekasi Regency. This research used a sample size of 93 students from the population of 1156 students of three Junior High Schools in Bekasi, selected with cluster random sampling technique. The study concluded with the following (1) there is a positive and significant relationship between learning independence and curiosity on science learning achievement, (2) there is a positive and significant relationship between independent learning and science learning achievement, and (3) there is a positive and significant relationship between curiosity and science learning achievement. Increasing students' learning independence and curiosity will result in better science learning achievement than only increasing students' learning independence or increasing student curiosity.